The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ygcen.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B and reproductive functions: “KNDy neuron” model in mammals and the emerging story in fish

Abstract: In mammals, neurokinin B (NKB), the gene product of the tachykinin family member TAC3, is known to be a key regulator for episodic release of luteinizing hormone (LH). Its regulatory actions are mediated by a subpopulation of kisspeptin neurons within the arcuate nucleus with co-expression of NKB and dynorphin A (commonly called the "KNDy neurons"). By forming an "autosynaptic feedback loop" within the hypothalamus, the KNDy neurons can modulate gonadotropin-releasing hormone (GnRH) pulsatility and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 173 publications
(288 reference statements)
1
33
0
1
Order By: Relevance
“…Molecular phylogeny showed that Clytia MIHR is not closely related to receptors of the core hypothalamus-pituitary-gonadal GPCRs, but rather forms a superfamily with receptors of these "upstream" neuropeptide hormones, notably GnIH, QRFP, Neuropeptide Y, and NkB. Production of GnRH and gonadotropins along the hypothalamus-pituitary-gonadal axis are inhibited by GnIH and stimulated by QRFPs [47,48], while the tachykinin family hormone NkB acts in a group of hypothalamus neurons together with kisspeptin and dynorphin A in the generation of cyclic GnRH pulses [49]. The ancestral cnidarian-bilaterian GPCR for MIHR and the receptors to all these vertebrate hormones may thus already have had a role in regulating gamete production and/or release.…”
Section: Evolution Of Reproductive Regulationmentioning
confidence: 99%
“…Molecular phylogeny showed that Clytia MIHR is not closely related to receptors of the core hypothalamus-pituitary-gonadal GPCRs, but rather forms a superfamily with receptors of these "upstream" neuropeptide hormones, notably GnIH, QRFP, Neuropeptide Y, and NkB. Production of GnRH and gonadotropins along the hypothalamus-pituitary-gonadal axis are inhibited by GnIH and stimulated by QRFPs [47,48], while the tachykinin family hormone NkB acts in a group of hypothalamus neurons together with kisspeptin and dynorphin A in the generation of cyclic GnRH pulses [49]. The ancestral cnidarian-bilaterian GPCR for MIHR and the receptors to all these vertebrate hormones may thus already have had a role in regulating gamete production and/or release.…”
Section: Evolution Of Reproductive Regulationmentioning
confidence: 99%
“…Molecular phylogeny showed that Clytia MIHR is not closely to receptors of the core H-P-G GPCRs, but rather forms a superfamily with receptors of these "upstream" neuropeptide hormones, notably GnIH, QRFP, Neuropeptide Y and NkB. Production of GnRH and gonadotropins along the H-P-G axis are inhibited by GnIH and stimulated by QRFPs [45,46], while the Tachykinin family hormone NkB acts in a group of hypothalamus neurons together with Kisspeptin and Dynorphin A in the generation of cyclic GnRH pulses [47]. The ancestral cnidarian-bilaterian GPCR for MIHR and the receptors to all these vertebrate hormones may thus already had a role in regulating gamete production and/or release.…”
Section: Evolution Of Reproductive Regulationmentioning
confidence: 99%
“…Kiss1-нейроны аркуатного ядра инфундибулярной области (группа КNDy-нейронов) участвуют в отрицательной обратной связи между половыми стероидами и гонадотропинами, обеспечивая тоническую секрецию ГнРГ, с участием динорфина (супрессора синтеза ГнРГ) и нейрокинина В (стимулятора синтеза ГнРГ). Они формируют аутосинаптическую петлю обратной связи и модулируют пульсативную секрецию ГнРГ и соответственно синтез ЛГ и ФСГ [30]. Kiss1-нейроны ростральной части поля III желудочка играют ключевую роль в передаче положительной обратной связи эстрадиола на гонадотропины, в первую очередь регулируя пульсативную активность гонадолиберина, в присутствии активированных рецепторов прогестерона, что инициирует преовуляторный пик ГнРГ [3,25,31] (рис.…”
Section: патофизиология приливов жара фокус на нейрогормональную регunclassified